Real-time object detection and classification of small and similar figures in image processing - Algorry, Aldo M. (2017)
Fil: Algorry, Aldo M. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales. Laboratorio de Computación; Argentina.